The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20040988
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and Raman Spectroscopy-Based Biochemical Profiling Reflects Genomic Diversity of Clinical Candida Isolates That May Be Useful for Diagnosis and Targeted Therapy of Candidiasis

Abstract: Despite the fact that Candida albicans is documented to be the main cause of human candidiasis, non-C. albicans Candida (NCAC) species, such as Candida glabrata and Candida tropicalis, are also suggested to be implicated in the etiopathogenesis of opportunistic fungal infections. As biology, epidemiology, pathogenicity, and antifungal resistance of NCAC species may be affected as a result of genomic diversity and plasticity, rapid and unambiguous identification of Candida species in clinical samples is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Zeitz et al [ 73 ] indicated that glycogen deficiency does not affect long-term survival, growth, metabolic flexibility or morphology of C. albicans . Similar results regarding the C. glabrata strain were obtained in our other studies [ 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…Zeitz et al [ 73 ] indicated that glycogen deficiency does not affect long-term survival, growth, metabolic flexibility or morphology of C. albicans . Similar results regarding the C. glabrata strain were obtained in our other studies [ 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…Two clinical Candida species isolates, namely Candida glabrata 4246 and Candida tropicalis 4114, were obtained from the Clinical Microbiology Laboratory (Department of Diagnostic Medicine, Provincial Medical Specialist Unit, Rzeszow, Poland) and comprehensively characterized elsewhere [64]. This study was approved by the Ethics Committee of the Faculty of Medicine, University of Rzeszow, Poland (approval code 2018/06/03, approved on 14 June 2018).…”
Section: Candida Species and Culture Conditionsmentioning
confidence: 99%
“…Over the past decade, both Raman and FTIR spectroscopy have become widely used in microbiology research on fungi [ 6 , 7 , 8 , 9 ] and bacteria [ 10 , 11 , 12 , 13 , 14 , 15 ]. FTIR spectroscopy is commonly applied for bacterial classification, with the ability to reach strain-level discrimination.…”
Section: Introductionmentioning
confidence: 99%